Presence of Bartonella spp in non-hematophagous bats in the Taricaya Ecological Reserve, Puerto Maldonado, Madre de Dios, Peru - Medrano Uchuya, Noelia (2022)
The aim of this study was to determine the presence of Bartonella spp in non-hematophagous bats in the Taricaya Ecological Reserve in Puerto Maldonado, Madre de Dios. In total, 62 bats of 16 species were captured using fog nets on 13 non-consecutive new moon nights. Blood samples (30 µl) were collected from the cephalic vein and poured onto Whatman FTA cards. DNA was extracted with a commercial kit and the diagnosis of Bartonella spp was made using the PCR technique, partially amplifying the citrate-synthase gene (gltA). Six bats were positive for the presence of Bartonella spp (9.68%), belonging to the species Carollia perspicillata, Artibeus lituratus, Phyllostomus elongatus and Platyrrhinus infuscus. The most abundant classification group according to the type of feeding was frugivorous (77.4%; 48/62), followed by omnivorous (12.9%; 8/62), where frugivorous species showed 83.3% (5/6) of results. positives. This is the first finding of Bartonella spp in A. lituratus, P. elongatus and P. infuscus.